Pulsed turbidite and methane seep records in the north western South China Sea since the last glacial maximum - Li, Jingrui; Miao, Xiaoming; Feng, Xiuli; Jiang, Rui; Zhao, Mengwei; Dan, Xiaopeng; Xiao, Qianwen; Wei, Jiangong (Frontiers in Marine Science, 2023)
The small-scale event layers in the continental margin contain abundant dynamic environment information, and pose a challenge to the interpretation of continuous sedimentary records, giving geological significance to their accurate identify and possible genesis. Here, pulsed turbidite layers since the last glacial maximum (LGM) in a gravity core in the northwestern South China Sea (SCS) was analyzed to investigate the precisely identification, possible causes and the role of marine environmental change during the late Quaternary in formation of these small-scale event layers in the SCS. Eight potential pulsed turbidite layers, according to the petrographic characteristics, grain size parameters and element geochemistry, were identified. Meanwhile, indicators including total sulfur (TS)/total organic carbon (TOC) ratio, CaCO3 content, and chromium-reducible sulfur (CRS) revealed these horizons were mostly related to methane seep events. Constrained by foraminifera shells AMS14C results, these events were determined to have occurred from the LGM to early Holocene, Similar records in the northern and southern slopes suggests the universal occurrence of these small-scale layers in the SCS. The comprehensive analysis showed that the development of these event layers over the past 25 ka can be divided into three stages, 25-15.5 ka, 15.5-7 ka and 7 ka to present. Late Quaternary Ocean environment changes, especially sea level and bottom water temperature, controlled the occurrence of regional small-scale event layers in the SCS. The regional scale mechanism is that the pressure and temperature change affect the stability of hydrate and the methane seepage, and thus the strata stability. Corresponding to the lowest, the rapid increase and the highest levels of the sea level and bottom water temperature, the temporal evolution pattern of small-scale event layers in the SCS showed a highest, decreased and lowest frequency, respectively. The linkage between the late Quaternary marine environmental change and turbidite deposition through gas activities in this study can act as a useful reference for further understanding the continental margin sedimentary process.